2007
DOI: 10.1074/jbc.m702155200
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Arrestin-Rhodopsin Interactions

Abstract: In this study we investigate conformational changes in Loop V-VI of visual arrestin during binding to light-activated, phosphorylated rhodopsin (Rho*-P) using a combination of site-specific cysteine mutagenesis and intramolecular fluorescence quenching. Introduction of cysteines at positions in the N-domain at residues predicted to be in close proximity to Ile-72 in Loop V-VI of arrestin (i.e. Glu-148 and Lys-298) appear to form an intramolecular disulfide bond with I72C, significantly diminishing the binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 40 publications
4
28
0
Order By: Relevance
“…73,86,109 In addition, the movement and/or structural rearrangement of the “finger loop” in the central crest of the receptor-binding side was also reported. 83,131 Both polar core and the three-element interaction clearly support the basal conformation in all arrestin structures, 1820,22 so their destabilization by the phosphates was consistent with the idea that global rearrangement is necessary for receptor binding. Partial destabilization of the interface between the two domains enhanced arrestin binding to inactive receptor, 132 again suggesting that arrestin conformation must change upon receptor binding.…”
Section: How Do Arrestins Fit Receptors?supporting
confidence: 72%
See 2 more Smart Citations
“…73,86,109 In addition, the movement and/or structural rearrangement of the “finger loop” in the central crest of the receptor-binding side was also reported. 83,131 Both polar core and the three-element interaction clearly support the basal conformation in all arrestin structures, 1820,22 so their destabilization by the phosphates was consistent with the idea that global rearrangement is necessary for receptor binding. Partial destabilization of the interface between the two domains enhanced arrestin binding to inactive receptor, 132 again suggesting that arrestin conformation must change upon receptor binding.…”
Section: How Do Arrestins Fit Receptors?supporting
confidence: 72%
“…18,19 Multiple residues in this loop were shown to be immobilized upon receptor binding in both arrestin-1 73 and -2. 71 Previous studies using fluorescent labels 131 and NMR 83 suggested that this loop extends and forms an α-helix upon receptor binding. Indeed, this loop was found to move in the direction of the receptor, although not as much as previously proposed, 131 and the data were consistent with its helical conformation in receptor-associated arrestin-1.…”
Section: How Do Arrestins Fit Receptors?mentioning
confidence: 99%
See 1 more Smart Citation
“…"Cysless" arrestin has been previously shown to retain wild-type function (32,33), and we verified that our mutant construct was functionally identical to native arrestin by centrifugal pulldown, light scattering, and extra Meta II analyses (data not shown). Single cysteine substitutions I72C, S344C, and A366C (see Fig.…”
mentioning
confidence: 70%
“…Labeling of these introduced cysteine residues with IANBD was performed as described previously for bimane (31). The concentration and labeling efficiency were determined using molar extinction coefficients of 0.025 M Ϫ1 cm Ϫ1 at 500 nm for IANBD (as reported by the manufacturer) and 0.02076 M Ϫ1 cm Ϫ1 at 278 nm for arrestin (33). When bound to the protein, IANBD was found to contribute no absorbance at 278 nm, and all mutants were labeled at near 100% efficiency.…”
mentioning
confidence: 99%